2010
DOI: 10.1021/jp108028d
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Electron Transfer Dynamics of a Terthiophene Carboxylate on Monodispersed Zinc Oxide Nanocrystals

Abstract: Photophysical data for solution phase mixtures of a new terthiophene based organic dye, 3′,4′-dibutyl-2-phenyl-2,2′:5′,2′′-terthiophene-5′′-carboxylic acid, and size selected, well-dispersed zinc oxide nanocrystals are reported. Time-resolved fluorescence and time- and frequency-resolved pump−probe spectroscopy confirm and characterize electron injection from the dye to the semiconductor nanocrystals (NCs) in room temperature ethanol dispersions at a series of dye:ZnO NC concentration ratios. The spectrum of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 88 publications
2
34
1
Order By: Relevance
“…The general shape of the Stern Volmer graphs observed for these dyes paralleled those reported in earlier studies, where the suggested causes were concentration quenching 21 or competition between dye binding sites that were or were not quenched. 3,4 The current work focused on the ultrafast quenching kinetics at a dye to ZnO NC of 2:1 in order to minimize any complications attributed to dye-dye interactions. 2T.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general shape of the Stern Volmer graphs observed for these dyes paralleled those reported in earlier studies, where the suggested causes were concentration quenching 21 or competition between dye binding sites that were or were not quenched. 3,4 The current work focused on the ultrafast quenching kinetics at a dye to ZnO NC of 2:1 in order to minimize any complications attributed to dye-dye interactions. 2T.…”
Section: Resultsmentioning
confidence: 99%
“…The lifetimes observed for 3T, 4T and 5T were similar to related terthiophene-based dyes that did not have cyanoacrylate anchoring groups. 3,5 The smallest dye, 2T, exhibited much shorter lifetimes. When ZnO NCs were combined with the dyes in an approximate 2:1 dye to NC ratio, a distinct transient absorption was observed that corresponded closely to the absorption observed from chemical oxidation of the dye using nitrosonium ion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Compound Time-integrated emission quenching and dye binding constant in detail in another study. 9,10 Time-resolved measurements Time correlated single photon counting Figure S5: Unmodified TCSPC raw data (points) and the biexponential fits used to determine electron injection timescales (lines). The instrument response is shown as the dotted line.…”
Section: Synthetic Detailsmentioning
confidence: 99%
“…16 In previous work we demonstrated that ZnO NCs quenched the excited state by electron transfer of two carboxylate-bound fluorophores, a terthiophene derivative and a zinc porphyrin. [17][18][19] Although capable of binding to the ZnO NCs, the ruthenium-polypyridyl complex, [Ru(bpy) 2 (dcbpy)](PF 6 ) 2 where bpy = 2,2′-bipyridine and dcbpy = 4,4′-dicarboxylic acid-2,2′-bipyridine, exhibited fluorescence that was not quenched. This was initially unexpected based on the reported fluorescence quenching of [Ru(bpy) 2 (dcbpy)] 2+ when it was bound to a colloidal ZnO film.…”
Section: Introductionmentioning
confidence: 99%